2018
DOI: 10.1002/jcp.27090
|View full text |Cite
|
Sign up to set email alerts
|

Regulation effects of melatonin on bone marrow mesenchymal stem cell differentiation

Abstract: Melatonin's therapeutic potential has been highly underestimated because its biological functional roles are diverse and relevant mechanisms are complicated. Among the numerous biological activities of melatonin, its regulatory effects on pluripotent mesenchymal stem cells (MSCs), which are found in bone marrow stem cells (BMSCs) and adipose tissue (AD-MSC), have been recently proposed, which has received increasingly more attention in recent studies. Moreover, receptor-dependent and receptor-independent respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 92 publications
1
37
0
2
Order By: Relevance
“…Recently, more and more studies have been carried out to investigate the effect of melatonin during differentiation of MSCs. It has been demonstrated that melatonin can significantly enhance osteoblast differentiation of MSCs [16]. Similarly, our previous works have showed that melatonin is significant in promoting the osteogenesis and chondrogenic differentiation of BMSCs [1721].…”
Section: Introductionmentioning
confidence: 82%
“…Recently, more and more studies have been carried out to investigate the effect of melatonin during differentiation of MSCs. It has been demonstrated that melatonin can significantly enhance osteoblast differentiation of MSCs [16]. Similarly, our previous works have showed that melatonin is significant in promoting the osteogenesis and chondrogenic differentiation of BMSCs [1721].…”
Section: Introductionmentioning
confidence: 82%
“…Melatonin is highly pleiotropic and regulates countless physiological parameters in numerous organs. 8,[28][29][30][31] Among them, several fields deserve particular emphasis, such as the control of circadian rhythms and, in photoperiodically sensitive species, of seasonality, both in conjunction with the transmission of the signal "darkness" [32][33][34] ; modulation of differentiation and growth [35][36][37] ; antioxidative protection by various mechanisms [38][39][40][41][42] ; anti-oncogenic and oncostatic actions [43][44][45] ; and, with particular relevance to this article, immune modulation. 16,[46][47][48][49] Physiological functions of macrophages go from host defense to immune downregulation, 50,51 in addition to their homeostatic activities.…”
Section: Introductionmentioning
confidence: 99%
“…We previously reviewed the roles of melatonin in cancer, ischemic heart diseases, fibrosis, and sepsis . Previous reviews have suggested that melatonin plays a pivotal role in bone . Recent studies have demonstrated that melatonin can protect against osteoporosis and maintain homeostasis of bone metabolism .…”
Section: Introductionmentioning
confidence: 99%
“…30 Previous reviews have suggested that melatonin plays a pivotal role in bone. 31,32 Recent studies have demonstrated that melatonin can protect against osteoporosis 33 and maintain homeostasis of bone metabolism. 34,35 In light of the emerging roles of melatonin in bone metabolism, the present review discusses recent breakthroughs related to melatonin in osteoporosis ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%